2021
DOI: 10.1016/j.phro.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

On-line daily plan optimization combined with a virtual couch shift procedure to address intrafraction motion in prostate magnetic resonance guided radiotherapy

Abstract: Background and purpose: In daily adaptive magnetic resonance (MR)-guided radiotherapy, plans are adapted based on the patient's daily anatomy. During this adaptation phase, prostate intrafraction motion (IM) can occur. The aim of this study was to investigate the efficacy of always applying a subsequent virtual couch shift (VCS) to counter IM that occurred during the daily contour and plan adaption (CPa) procedure. Material and Methods: One hundred fifty patients with low and intermediate risk prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…However, a PTV margin reduction to <5 mm will likely result in an increased number of ATP plans after ATS on the MR-Linac, further increasing overall treatment time. The advantage of ATP after ATS is that it may help account for the additional motion, and this has been noted by [7] , where ATP after every ATS fraction resulted in a reduction in prostate drift in the posterior and inferior direction and can help decrease the bladder volume in the high dose region. However, with longer treatment times, there would be an increased likelihood of intrafraction motion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a PTV margin reduction to <5 mm will likely result in an increased number of ATP plans after ATS on the MR-Linac, further increasing overall treatment time. The advantage of ATP after ATS is that it may help account for the additional motion, and this has been noted by [7] , where ATP after every ATS fraction resulted in a reduction in prostate drift in the posterior and inferior direction and can help decrease the bladder volume in the high dose region. However, with longer treatment times, there would be an increased likelihood of intrafraction motion.…”
Section: Discussionmentioning
confidence: 98%
“…There is an opportunity to explore PTV margin reduction based on these results or personalized PTV margins considering the extent of target coverage change and displacement varied between patients. However, PTV reduction to <4 mm should be implemented with caution due to intrafraction motion over the course of treatment adaptation [7] , [14] . It has been shown that over the course of a 10-minute cine imaging session reflective of treatment delivery time on a MR-Linac; using fiducial markers as a prostate tracking surrogate, translation trends of 1 mm posterior and 0.9 mm inferior occur [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In such instances, we hypothesize that the large magnitude of the deformations together with the significantly different image features introduced by the gas pocket itself has led to the algorithm converging towards a local minimum and in turn causing a local misregistration. Our previous work on intra-fraction motion indicated that these rectal deformations are unpredictable and non-gradual [1] , [14] , [22] , [23] . Especially cases with large rectal deformations could benefit from an adaptive workflow and therefore warrant extra time to assure contours are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…During the treatment plan calculation, an online 3D T2w position verification MR scan was made. The position verification scan was used to perform an additional ATP procedure directly before beam on to account for intratreatment patient motion during the ATS procedure [10] , [11] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%